2010
DOI: 10.1680/geng.2010.163.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of tunnels from a basement excavation in London

Abstract: A site in central London called One New Change is currently being redeveloped. The new development has a basement that extends to approximately 14 m below ground level. Demolition of the building that formerly occupied the site, excavation of the new basement and construction of the new development have caused unloading and subsequent reloading of the ground. This change of loading has resulted in displacements occurring to the nearby London Underground Central Line tunnels that run parallel to the northern bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…It has been possible to determine that metro infrastructure not only has a physical presence affecting the built environment (Devriendt et al, 2010;Perry, 2014;Simpson and Vardanega, 2014) but also a statutory and legal presence. (Defining 'statutory' as meaning that the metro has a right to be present within its environment through its specific enabling legislation and that it must accommodate the statutory rights of other parties, such as utility providers and other transport organisations, and 'legal' as being through contractual agreements for acquisition and disposal of land by the metro company or third parties, or for a right of the metro infrastructure to be located within the land of another party through easements or servitudes.)…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been possible to determine that metro infrastructure not only has a physical presence affecting the built environment (Devriendt et al, 2010;Perry, 2014;Simpson and Vardanega, 2014) but also a statutory and legal presence. (Defining 'statutory' as meaning that the metro has a right to be present within its environment through its specific enabling legislation and that it must accommodate the statutory rights of other parties, such as utility providers and other transport organisations, and 'legal' as being through contractual agreements for acquisition and disposal of land by the metro company or third parties, or for a right of the metro infrastructure to be located within the land of another party through easements or servitudes.)…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
“…Any of these may be incorporated within or adjacent to the subsoil, land space and airspace or buildings of another party (Baker, 1885). The method of construction of the metro and the strata through which it passes not only affects adjacent land and buildings but can also be affected by redevelopment of that land and those buildings (Devriendt et al, 2010;Glass and Stones, 2000;Macklin and Yeow, 2004;Measor and Williams, 1962;Perry, 2014;Simpson and Vardanega, 2014). Therefore, the presence of the metro infrastructure must be clearly understood and accommodated ( would require any future development of this site to accommodate the presence of the station from physical and legal perspectives, physically ensuring the long-term presence and operability of the engineered structures while seeing some acquisition of the land, subsoil and airspace above and around it.…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
“…Among them, the three-dimensional finite element method can consider the complex boundary conditions and the interaction between structures and its surrounding soil. Therefore, it is widely used in the study of the influence of foundation pit excavation on adjacent tunnels [11][12][13]. However, it requires professional software and substantial computational effort, and it is only suitable for obtaining some details in a final design rather than as a preliminary routine design tool [14].…”
Section: Introductionmentioning
confidence: 99%
“…For the convenience of shoppers and users, there is an increasing demand for deep basements for buildings which are located close to or directly above existing tunnels (Burford, 1988;Chang et al, 2001;Sharma et al, 2001;Devriendt et al, 2010;Liu et al, 2011b). Burford (1988) reported measured maximum heaves of 50 mm and 41 mm in existing twin tunnels due to an overlying 12 m deep excavation in London clay.…”
Section: Introductionmentioning
confidence: 99%
“…Cracks were observed in the reinforced concrete segments and the concrete slab at the tunnel invert was displaced. Devriendt et al (2010) reported displacements of twin tunnels due to a nearby 14 m deep basement excavation. The twin tunnels with C/D ratios of 5.8 and 6.7 were located at a side of the basement with a minimum distance between them of 7.2 m (0.51 H e ).…”
Section: Introductionmentioning
confidence: 99%